Turnkey fibre bragg grating interrogator for real-time static and dynamic monitoring applications - Mohd Hafizi, Zohari; Epin, Vorathin; Nur Ainaa Adhreena, Muhamad Shukri (Institution of Engineering and Technology, 2022)
Fibre Bragg Grating (FBG) sensors have been widely known for the capability of per-forming static and dynamic measurements. However, the commercially available interrogators have several limitations such as low sampling frequency, lack of complete product that is ready for immediate use and the need of highly skilled FBG experts to interpret the readings. Therefore, this study demonstrated on the improved FBG interrogator known as Universiti Malaysia Pahang -Fibre Bragg Grating Interrogator (UMP-FBGI). Prediction of flexural load on composite beam is carried out for static monitoring. The results revealed that UMP-FBGI possessed good repeatability with the highest percentage of error at 7.51%. For dynamic monitoring evaluation, natural frequency of the composite beam is determined. From the comparison with accelerometer, the highest percentage of error is obtained at 9.82%. All in all, the developed FBG interrogator is a complete product with real-time monitoring graphical user interface (GUI) ready for immediate use.